METODE PEMBELAJARAN BLEANDED LEARNING DENGAN MODEL FLEX PADA MATA PELAJARAN GAMBAR TEKNIK - Yogi Pradana (CV. ADIBA AISHA AMIRA, 2025)
Blended Learning is a learning method that integrates online learning with traditional methods that require the physical presence of teachers and students in the classroom. During the COVID-19 pandemic, Blended Learning allows the use of applications such as WhatsApp and Google Classroom for online learning. The focus of this research is the use of AutoCAD in teaching technical drawing at vocational schools. AutoCAD was chosen because of its superiority in accuracy, efficiency, and ability to produce three-dimensional drawings. However, some students face difficulties in understanding drawing learning with AutoCAD, which has a negative impact on their learning process. Therefore, the Flex model in Blended Learning is used to increase learning effectiveness. This model gives students control over their own learning path with face-to-face support from teachers. In the context of online learning, teacher creativity and parental support are very important to create a fun and productive learning environment for students. Online learning can also increase student independence, discipline and creativity, although it requires readiness from all parties involved.